2003
DOI: 10.1007/s10267-002-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic karyotype of Flammulina velutipes and its variation among monokaryotic progenies

Abstract: The karyotype of Flammulina velutipes (Curt. : Fr.) Sing. was investigated using contour-clamped homogeneous electric fields (CHEF) gel electrophoresis. A parental dikaryotic stock, JA, was resolved into at least eight chromosomal DNA bands ranging from 1.4-to 4.9-megabase (Mb) pairs. Overall, little size variation was found among monokaryotic strains with a few major exceptions. Among 13 monokaryotic progenies examined, 11 strains were resolved into at least eight chromosomal DNA bands in a manner similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
10
1
1
Order By: Relevance
“…The electrophoretic karyotype of FSB presented here is slightly different from those previously reported for other cultivated varieties of F. velutipes; for example, Japanese variety ''Nakano-JA'' has seven or eight haploid chromosomes ranging from 1.4 to 4.9 Mb, with total sizes of 24.0-24.6 Mb (Tanesaka et al 2003), and the karyotype from a Korean commercial variety has six or seven haploid chromosomes ranging from 1.60 to 5.84 Mb, with total sizes of 23.98-26.98 Mb (Park et al 2010). The CLP between parental monokaryons, omFSB1 and omFSB2, presented here and also that observed in a Korean variety (Park et al 2010) is relatively large in comparison with the CLP among monokaryotic progeny generated from basidiospores (Tanesaka et al 2003). It is unclear whether the size differences among monokaryons are attributable to a property of individual dikaryons or to other effects, i.e., selection during the meiotic process or spore germination, or afterward to eliminate karyotype aberration among progeny.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…The electrophoretic karyotype of FSB presented here is slightly different from those previously reported for other cultivated varieties of F. velutipes; for example, Japanese variety ''Nakano-JA'' has seven or eight haploid chromosomes ranging from 1.4 to 4.9 Mb, with total sizes of 24.0-24.6 Mb (Tanesaka et al 2003), and the karyotype from a Korean commercial variety has six or seven haploid chromosomes ranging from 1.60 to 5.84 Mb, with total sizes of 23.98-26.98 Mb (Park et al 2010). The CLP between parental monokaryons, omFSB1 and omFSB2, presented here and also that observed in a Korean variety (Park et al 2010) is relatively large in comparison with the CLP among monokaryotic progeny generated from basidiospores (Tanesaka et al 2003). It is unclear whether the size differences among monokaryons are attributable to a property of individual dikaryons or to other effects, i.e., selection during the meiotic process or spore germination, or afterward to eliminate karyotype aberration among progeny.…”
mentioning
confidence: 55%
“…By this method, electrophoretic karyotypes have been revealed for many fungi including cultivated edible mushrooms such as A. bisporus (Royer et al 1991(Royer et al , 1992Sonnenberg et al 1991;Lodder et al 1993), L. edodes (Arima and Morinaga 1993), Pleurotus species (Sagawa and Nagata 1992;Tamai et al 1995), and F. velutipes (Kim et al 2000;Tanesaka et al 2003;Park et al 2010). Various reports have suggested that F. velutipes has at least six (Kim et al 2000), or six or seven (Park et al 2010), or seven or eight (Tanesaka et al 2003) haploid chromosomes. Chromosome-specific probes have also been constructed by assignment of DNA probes prepared from a cDNA library to CHEF-separated chromosomes (Kim et al 2000;Park et al 2010).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Sixteen out of 40 random primers amplified polymorphic RAPD fragment patterns. The polymorphic levels of RAPD bands by some primers 4,3,9,10,20) were very high in all 29 strains, with 3,030 fragments ranging between 200 and 2,000 bp. Intraspecific genetic dissimilarity of the 29 strains was calculated to range from 3.3% to 45% by Nei-Li's method using these 3,030 RAPD bands.…”
mentioning
confidence: 97%
“…팽이버섯 자실체 색의 유전양식과 자실체와 연관된 분자마 커 [1,12], 팽이 수집 품종들에 대한 RAPD 분석 [14], RAPD에 의한 단포자의 유전적 변이 [13], 팽이버섯 발생에 따른 EST (expressed seguence tags) [9,25], genome의 크기와 핵형 [10,20] 등이 보고된 바 있고, 현재 팽이버섯 유전체를 밝히고 자 하는 연구가 진행되고 있다. 그러나 팽이버섯은 세계적으로 200여 종류의 품종이 있지 만 품종들을 식별하고 이를 바탕으로 교배육종을 설계 혹은 품종평가를 할 수 있는 분자유전적 보고는 일부분에 불과하 다.…”
unclassified